Determinants of Non-Performing Bank Loans Listed on The Indonesia Stock Exchange For The 2016-2020 Period - Irfan Setyo Nugroho; Endri Endri (Syntax Corporation Indonesia, 2022)
This study aims to analyse the effect of BOPO, Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), Net Interest Margin, Oil Price, inflation, and Interest Rate on Non-performing Loans (NPL) of banks listed on the Indonesia Stock Exchange during 2016-2020. The total population of banks listed on the IDX is 46 banks. In contrast, the sample in this study is part of the population, which is 32 banks. This study is quantitative, so the data analysis method used is a statistical method—the analysis of these data using Econometric Views (Eviews) software version 12.0. The results showed that BOPO has a positive and significant effect on bank NPLs, LDR has a positive but not significant effect on NPLs, CAR has a negative and significant effect on NPLs, NIM has a negative and significant effect on NPLs, Oil Price has a positive and significant effect on NPLs, inflation has a negative but not significant effect on NPLs, and Interest Rate has a positive and significant effect on NPLs. Banks must pay attention to the reference and rules of the regulator, the Financial Services Authority, as a guideline where the maximum limit for the NPL ratio is 5% so that the quality of banking credit can be maintained. Investors it is expected to be able to make considerations in investing by analyzing the company's condition through financial statements published by banks by looking at the ratio of Non-Performing Loans as a crucial consideration.